(untitled) (Journal of Multidisciplinary Sciences and Innovations, 2025)
This article discusses the theoretical foundations, technological solutions and effectiveness of using electro technological methods to eliminate diseases in fruit trees. Scientific analyses of the effects of electric field, pulsed current and electro plasma technology on plant physiology, in comparison with traditional chemical treatment methods, are presented. The studies demonstrate the environmental safety, minimal resource consumption and high efficiency of electro technological treatment.